MEKANISME PASAR PENDEKATAN RETROSFEKTIF EKONOMI ISLAM - Muzakkir, Ahmad Zaky (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2020)
ABSRACTMarket is the most visited place by the public. The market in Islamic view of economy requires morality in all economic activities, in particular : fair and healthy competition, honesty, transparancy, and fairness. The concept of market mechanisms in Islam is built on principles, that is: Ridho each other, healthy competition, honesty, transparency, and justice. Islam has tightened its people